Review of chloride and sulphate attenuation in ground water nearby solid‐waste landfill sites - Venkatesan, G.; Swaminathan, G. (Journal of Environmental Engineering and Landscape Management, 2009)
Paper review "Review of chloride and sulphate attenuation in ground water nearby solid‐waste landfill sites". Journal of Environmental Engineering and Landscape Management 17(1): Ia-Ig.Ground water drawn for  various purposes, such as irrigation, drinking and industrial, is constantly on the rise in areas where surface water are sources nowadays scarce due to erratic rainfall and  climatic conditions. Chloride and sulphate in ground water increase due to municipal and industrial waste dumped on the ground surface. Elevated concentration  of  chloride  (Cl-)  and  sulphate  (SO4-) in  surface  and  ground  water  are  common  in  all  countries,  and  can  serve  as  indicators  of  ground  water  pollution.  We have  to  characterize  the  most  prevalent  natural  and  anthropogenic  sources  of  chloride and sulphate in ground water and explore techniques that could be used to  identify their source. There is an urgent need for additional solid-waste management capacity sites in many parts of developing countries. Current design, operation,   closure,   and   post-closure   activities   for   sanitary   landfills   do   not guarantee   sufficient   public   health   and  environmental  protection  of  the  groundwater resources near  a  landfill.  While  in  the  past,  sanitary  landfills  have  almost  without exception contaminated ground waters in the vicinity of  a landfill. Due to scarcity of hand, to many urban localities, people never mind having residents near by a landfill site. Significant changes must be made in the approach used for landfill of metropolitan solid wastes. Chloride and sulphate may be taken as critical  parameters in  assessment of ground water quality.Chloridų ir sulfatų mažinimo požeminiame vandenyje šalia sąvartynų problemosSantrauka. Rajonuose,  kur  paviršinio  vandens  dėl  kritulių  nepastovumo  ir  klimatinių sąlygų nepakanka, yra pakilęs  požeminio  vandens,  naudojamo  drėkinimui,  gėrimui,  pramonėje,  lygis.  Dėl  komunalinių  ir  pramoninių  atliekų sąvartynų  požeminiame  vandenyje  padaugėja  chloridų  (Cl–)  ir  sulfatų  (SO4–).  Jų  koncentracijų  padidėjimas  paviršiniame  ir  požeminiame  vandenyje  dažnas  visose  šalyse,  tuo  galima  remtis  kaip  požeminio  vandens  taršos  indikatoriumi.  Turime  apibūdinti  labiausiai  paplitusius natūralius ir antropogeninius chloridų ir sulfatų šaltinius, teršiančius požeminį vandenį, ir ištirti metodus, kuriuos galima būtų taikyti šaltiniams nustatyti. Daugelyje besivystančių šalių būtinos papildomos atliekų tvarkymo vietos. Dabartinis  komunalinių atliekų sąvartynų  projektavimas,  eksploatavimas,  uždarymas  ir  atkūrimas  negarantuoja  pakankamos  požeminio  vandens  išteklių  apsaugos  sąvartynų įtakos  zonoje  gyvenančių  žmonių  sveikatos  ir  aplinkos  atžvilgiais.  Praeityje komunalinių atliekų sąvartynai, beveik visi be išimties, teršė požeminį vandenį toje teritorijoje. Dėl patirties stokos daugelyje urbanizuotų teritorijų nekreipta dėmesio į gyvenančius netoliese. Reikšmingi pokyčiai turi būti padaryti dėl sąvartynų,  kuriuose  šalinamos didmiesčių atliekos,  tvarkymo.  Chloridų  ir  sulfatų  kiekiai  gali  būti  laikomi  kritiniais  parametrais požeminio vandens kokybei vertinti.Reikšminiai žodžiai: požeminis vanduo, chloridai, užkastos atliekos, sulfatai, atliekos.Уменьшениe хлоридов и сульфатов в подземных водах вблизи свалокРезюме. Потребляемость подземной воды для полива, питья, промышленных нужд увеличена в тех районах, в которых поверхностной воды не достаточно из-за непериодических осадков и климатических условий. В таких водах количество хлоридов и сульфатов оказывается увеличенным из-за коммунальных и промышленных отходов на свалках. Увеличение концентраций хлоридов  (Cl–) и сульфатов  (SO4–) вповерхностныхиподземныхводах  –  явление, часто наблюдаемое во всех странах. Этот фактор может рассматриваться как индикатор загрязненностиподземнойводы. Авторы стать и ставили целью охарактеризовать наиболее распространенные естественные и антропогенные источники хлоридов и сульфатов, загрязняющих подземные воды, и исследовать методы, которые могут применяться для очищения таких источников. Во многих развивающихся странах необходимо обору-дование дополнительных мест для отходов. Современные способы проектирования, эксплуатации, закрытия и открытия новых мест свалок не гарантируют достаточную защиту источников подземных вод в зоне свалок относительно здоровья людей и охраны окружающей среды. Особое внимание должно уделяться свалкам, на которые вывозятся отходы из больших городов. Хлориды и сульфаты могут использоваться в качестве критических параметров для оценки качества подземных вод.Ключевые слова: подземныеводы, хлориды, свалки, сульфаты, отходы.First Published Online: 14 Oct 2010